Pencegahan Perilaku Perundungan (Bullying) pada Pelajar SMP Al-Khaairat Kota Ternate - Rada, Arisa Murni; Aslan Hasan (Nuban Jaggadhita Center, 2024)
T The purpose of this legal counseling session is to enhance the understanding of students and school staff about bullying behavior, its consequences, and to strengthen their legal awareness. This activity aims to provide comprehensive insights into bullying and its legal aspects, while also motivating participants to actively engage in preventing and addressing bullying cases in the school environment. Methodology: The session used a lecture method, where the speakers from the Community Service Team of the Faculty of Law, Universitas Khairun, presented material on bullying, its various forms, its impacts, and cyberbullying as a current phenomenon. This was followed by a discussion session and an evaluation through a quiz. Findings: The result of this activity was the successful implementation of the legal counseling session on Saturday, April 27, 2024, held at the Al-Khairaat Mosque Complex in Ternate City. The event was attended by 56 students. The speakers delivered material on the types of bullying, both verbal and non-verbal, and its impact on victims. Additionally, legal consequences for perpetrators of bullying were discussed, as well as measures that schools, parents, and students themselves can take to prevent and address bullying.